Ecological efficiency of renewable and non-renewable energy generation power systems considering life cycle assessment - de Paula Santos, Caio Felipe [UNESP]; Bimestre, Thiago Averaldo [UNESP]; Tuna, Celso Eduardo [UNESP]; Silveira, José Luz [UNESP] (Springer Nature, 2022)
The world consumption of electricity has been increasing exponentially over the years; consequently, there is an increase in atmospheric emissions. In addition, the diversity of electricity generation sources is increasing, and renewable sources are becoming more popular because they are considered renewable energy sources with low atmospheric emissions. This work presents an original contribution from a comprehensive technical review of the current state of the art of the ecological efficiency method and the application of life cycle analysis in electricity generation systems, both renewable and non-renewable. As an original contribution, this article aims, for the first time, to solve the ecological efficiency difficulty in finding values for renewable energy generation systems and thus be able to compare with conventional systems when investigating the influence of life cycle analysis results. The results show that for full load operation, the minimum ecological efficiency was approximately 76.93% for hydro plants, 84.72% for solar PV and 95.10% for wind power. The contributions of this work can make public policy decision-making in the choices of energy generation systems simplifying the understanding of laypeople and experts during the process, making them understand that the consequences of indirect greenhouse gas emissions are as harmful or more than direct emissions, as they are not normally accounted for on plants.
Keywords: Energy systems; Greenhouse gas emissions; Life cycle impact analysis; Renewable and sustainable energy